The Necessity of Studio Art as a Site and Source for Dissertation Research. - Baxter, Kristin; Ortega López, Hugo; Serig, Dan; Sullivan, Graeme (International Journal of Art & Design Education, 2008)
The issue raised by the authors in this article question why studio art continues to be ignored as a site and source for research in art education. The necessity of the field to be able to participate within the research community in addressing cultural, social, educational and political concerns is acknowledged. It is argued, however, that the exclusive use of methods of inquiry that align with the conventions of social science research has been done at the expense of fully appreciating the capacity of artistic research undertaken in studio contexts. This tendency is especially prevalent in doctoral research in higher education. Three accounts of dissertation research are given that incorporate studio activity as a central agency of inquiry in conceptualising and theorising issues. Each highlights the capacity of art practice to reveal insights that are a consequence of what the researcher did in the studio setting as issues, ideas and interpretive stances emerged, and problems were re-conceptualised. What is different in these accounts from more mainstream approaches to research is the readiness to accept that constructing new knowledge is a creative and critical process.